Intraoperatively Observed Lacrimal Obstructive Features and Surgical Outcomes in External Dacryocystorhinostomy - Lee, Min Joung; Khwarg, Sang In; Kim, In Hyuk; Choi, Jeong Hoon; Choi, Youn Joo; Kim, Namju; Choung, Ho-Kyung (Korean journal of ophthalmology, 2017)
To analyze the features of lacrimal drainage system obstruction confirmed during external dacryocystorhinostomy surgeries and report the surgical outcomes. We reviewed the medical records of a total of 769 cases who underwent external dacryocystorhinostomy for primary lacrimal drainage obstruction between 2005 and 2014. Data about detailed location and extent of obstruction were collected intraoperatively. The sites of obstruction were classified into nasolacrimal duct obstruction (NLDO), common canalicular obstruction (CCO), and canalicular obstruction. Lacrimal sac mucosa and lumen were grossly inspected, and the frequency of lacrimal sac changes, such as significant inflammation or fibrosis, was analyzed in cases of CCO or canalicular obstruction. The surgical success rate was also evaluated including effect of lacrimal sac status in the CCO and canalicular obstruction groups. Of 769 cases, primary NLDO with patent canaliculi was diagnosed intraoperatively in 432 cases (56.2%), CCO in 253 (32.9%), and canalicular obstruction in 84 (10.9%). Of 253 cases with CCO, 122 (48.2%) showed clear lacrimal sac lumen, and the other 131 (51.8%) showed significant inflammation or fibrosis of the lacrimal sac. In cases with canalicular obstruction, 35 of 84 (41.7%) showed a clear lacrimal sac, and the other 49 cases (58.3%) cases revealed mucosal changes of the lacrimal sac. The functional success rate was 87.5% for primary NLDO, 75.5% for CCO, and 72.6% for canalicular obstruction. In the CCO group, the functional success rate was lower in cases with significant lacrimal sac change (p = 0.044). Even in patients with CCO or canalicular obstruction, a large number of cases have lacrimal sac changes, and those changes were associated with lower functional success rate.